The effect of periodized strength training and periodized concurrent training on running performance - Fiolo, N. (2017)
The objective of this dissertation was to evaluate the changes in preparedness over the course of training for a marathon in two well-trained runners. The athletes completed periodized strength training or a periodized concurrent training. This dissertation consisted of two separate investigations: